Analisis Perbandingan Kinerja Keuanagan Bank Syariah dan Bank Konvensional Indonesia - Ashilah Razaktania Widodo; Fauzatul Laily Nisa (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
In the current age of globalization, it is inevitable that there is competition in various sectors of the economy, including banking. which is why Islamic banks and regular banks are facing more competition. Nowadays, businesses compete with one another to draw in new clients and hold onto their current clientele. This study aims to show the differences that exist between the progress of Islamic banking performance and conventional banking with the hope of increasing bank performance through this strategy to escalate the customers and increase profits. The effect of bank performance appraisals can be utilized to understand future business strategies and to assess how effective the implementation of the company's operational policies and activities is. This study used descriptive literature methodology to use secondary data. The study’s conclusion indicate that Islamic banking and conventional banking are dissimilar in terms of financial performance, based on financial statements, credit, as well as savings systems